Стратегії забезпечення стійкості бізнесу в умовах невизначеності: тренди, ризики та адаптивні моделі - Галушка, Зоя Іванівна (Sergeieva&Co Karlsruhe, Germany, 2025)
The paper examines contemporary strategies for ensuring business resilience under conditions of global uncertainty. It substantiates the transition from crisis response to systemic strategic adaptability that integrates technological innovation, flexible management, investment in human capital, and social responsibility. The study highlights the role of generative artificial intelligence, digitalization, ESG approaches, client-centric business models, and cross-sector partnerships in building resilient organizational systems. Global megatrends for 2025–2030 are identified as key determinants of the emerging paradigm of economic development and business resilience.
STRATEGIES FOR ENSURING BUSINESS RESILIENCE UNDER UNCERTAINTY: TRENDS, RISKS, AND ADAPTIVE MODELS
Keywords: business resilience, uncertainty, adaptive management, innovation model, ESG strategy, artificial intelligence, partnerships, economic transformation.